2022
DOI: 10.3390/jof8111212
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Strains with Identical Genomes Were Found at a Distance of 2000 Kilometers after 40 Years

Abstract: Heredity and variation are inherent characteristics of species and are mainly reflected in the stability and variation of the genome; the former is relative, while the latter is continuous. However, whether life has both stable genomes and extremely diverse genomes at the same time is unknown. In this study, we isolated Sclerotinia sclerotiorum strains from sclerotium samples in Quincy, Washington State, USA, and found that four single-sclerotium-isolation strains (PB4, PB273, PB615, and PB623) had almost iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
0
0
0
Order By: Relevance
“…This was further confirmed by the complete MLST sequence and UP-PCR profile identity of French and New Zealand isolates, as reported in Figure 4 [47][48][49]. Studies on the diversity within the Sclerotiniacae family showed that variability among strains can be very high [50], but it can also be very limited in space and time [51], suggesting the need to better decipher the different genetic backgrounds of Sclerotiniaceae undergoing fast genetic changes, or on the contrary, high genetic stability.…”
Section: Discussionsupporting
confidence: 55%
“…This was further confirmed by the complete MLST sequence and UP-PCR profile identity of French and New Zealand isolates, as reported in Figure 4 [47][48][49]. Studies on the diversity within the Sclerotiniacae family showed that variability among strains can be very high [50], but it can also be very limited in space and time [51], suggesting the need to better decipher the different genetic backgrounds of Sclerotiniaceae undergoing fast genetic changes, or on the contrary, high genetic stability.…”
Section: Discussionsupporting
confidence: 55%